Analisis Pengaruh Kualitas Sumber Daya Manusia Koperasi dan Infrastruktur Ekonomi Terhadap Pertumbuhan Ekonomi di Indonesia - Fefy Finasri; Mike Triani (Universitas Negeri Padang, 2023)
This study explains the extent to which the Quality of Human Resources, Cooperatives, and Economic Infrastructure Affect Economic Growth in Indonesia. The data sources used in this research are secondary data and data from 2013 to 2020 in 34 provinces of Indonesia. This study used descriptive analysis and inductive analysis. Inductive analysis can be tested with several tests, namely: (1) Panel Regression (2) Classical Assumption Test (3) T test and (4) F test. The variables used in this study are the Quality Of Human Resources (X1) Cooperatives (X2) Economic Infrastructure (X3) and Economic Growth (Y), using panel data; it was found that (i) the Quality Of Human Resources had a positive and significant effect on Economic Growth in Indonesia (ii) Cooperatives had a negative and insignificant effect on Economic Growth in Indonesia (iii) Economic Infrastructure had a positive and insignificant effect on Economic Growth in Indonesia (iv) overall, the independent variables in this study have a significant effect on Economic Growth in Indonesia.